Antimicrobial effect of Manuka honey and Kanuka honey alone and in combination with the bioactives against the growth of Propionibacterium acnes ATCC 6919 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Albany, New Zealand - Wu, Qiong; Wu, Qiong (Massey University, 2011)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicle. The Propionibacterium acnes (P. acnes) play a key role in inflammation and the formation of comedones. P. acnes has been reported to develop antibiotic resistance, which has generated some interest in developing natural antimicrobial compounds which forms the subject matter of this study. Recently, Manuka honey (leptospermum scoparium) has demonstrated strong antibacterial activities against a wide range of pathogens with distinct non-peroxide activity. Kanuka honey has also shown to be effective against many bacterial species. Many natural bioactives were reported to possess strong antibacterial activities, a few of which were studied against P. acnes. Therefore, the aims of this study were to investigate the antibacterial activity of Manuka honeys and Kanuka honey with and without catalase against the growth of P. acnes alone and to screen the antibacterial activities of five selected nature bioactives alone and in combination with honey against P. acnes in vitro. Methods: The growth of P. acnes was evaluated under aerobic and anaerobic conditions. P. acnes was cultivated in nutrient broth and fastidious anaerobic agar containing horse blood. Manuka honeys 20+, 15+ and 10+ UMF and Kanuka honeys were tested against the growth of P. acnes, ranging from 0.5 % to 12.5 % (w/v) with and without catalase under both aerobic and anaerobic conditions. The artificial honey was used as the control. Manuka tree essential oil (MTO), lavender essential oil (LO), green tea extract (GTE), olive leaves extract (OLE), propolis were screened using disc diffusion method, spectrophotometric assay, viable cell counts to determine the survival of P. acnes in the bioactives testing solutions. The combination creams of Manuka honey 10+ UMF (10 %, w/v) with bioactives were studied using viable cell count method to determine the viable cells of P. acnes. Results: P. acnes is capable of growing under both aerobic and anaerobic conditions. Manuka and Kanuka honeys exhibited antibacterial activity against the growth of P. acnes. Kanuka honey had similar antibacterial activity as Manuka honey 15+ UMF and Manuka honey 20+ UMF without catalase. MIC100 of Manuka honey 20+ UMF was 148.90 mg/mL; MIC100 of Manuka honey 15+ UMF was 125.81 mg/mL; MIC100 of Manuka honey 10+ UMF was 144.43 mg/mL; MIC100 of Kanuka honey was 123.28 mg/mL. Manuka honeys possessed non-peroxide activity, but the antibacterial activity of Kanuka honey decreased significantly after the removal of hydrogen peroxide with MIC100 of 549.21 mg/mL. Artificial honey did not markedly inhibit the growth of P. acnes. Among the five bioactives, only GTE and MTO had bactericidal ability. Honey creams with bioactives showed that cream containing 10 % honey and 1 % GTE caused about five log reductions in the bacterial cell numbers; in contrast, cream of honey (10 %) and MTO (0.125 %) resulted in about two log reductions. No bacterial cells (< 100 CFU/mL) were found in the creams containing honey (10 %), MTO (0.125 %) and GTE (1 %). Conclusion: Manuka honey exhibited antibacterial activity against the growth of the P. acnes. The antibacterial potency of the honey was significantly enhanced by the presence of bioactives in the emulsion cream.
Keywords: Honey; Antibacterial agents; Acne